High-resolution cerebral blood flow simulation with a domain decomposition method and verified by the TCD measurement. (September 2022) - Zhou, Jie; Li, Jing; Qin, Shanlin; Liu, Jia; Lin, Zeng; Xie, Jian; Zhang, Zhijun; Chen, Rongliang
Highlights: A parallel scalable method is proposed for the high-resolution simulation of blood flows in a patient-specific full precerebral artery. The proposed algorithm can scale up to thousands of processors and do one cardiac cycle simulation of a standard cerebral case within one hour. The simulated results agree well with the clinical data measured by transcranial Doppler ultrasound. Abstract: Background: An efficient and accurate blood flow simulation can be useful for understanding many vascular diseases. Accurately resolving the blood flow velocity based on patient-specific geometries and model parameters is still a major challenge because of complex geomerty and turbulence issues. In addition, obtaining results in a short amount of computing time is important so that the simulation can be used in the clinical environment. In this work, we present a parallel scalable method for the patient-specific blood flow simulation with focuses on its parallel performance study and clinical verification. Methods: We adopt a fully implicit unstructured finite element method for a patient-specific simulation of blood flow in a full precerebral artery. The 3D artery is constructed from MRI images, and a parallel Newton–Krylov method preconditioned with a two-level domain decomposition method is adopted to solve the large nonlinear system discretized from the time-dependent 3D Navier-Stokes equations in the artery with an integral outlet boundary condition. The simulated results are verified using the clinical data measured by transcranial Doppler ultrasound, and the parallel performance of the algorithm is studied on a supercomputer. Results: The simulated velocity matches the clinical measured data well. Other simulated blood flow parameters, such as pressure and wall shear stress, are within reasonable ranges. The results show that the parallel algorithm scales up to 2160 processors with a 49% parallel efficiency for solving a problem with over 20 million unstructured elements on a supercomputer. For a standard cerebral blood flow simulation case with approximately 4 million finite elements, the calculation of one cardiac cycle can be finished within one hour with 1000 processors. Conclusion: The proposed method is able to perform high-resolution 3D blood flow simulations in a patient-specific full precerebral artery within an acceptable time, and the simulated results are comparable with the clinical measured data, which demonstrates its high potential for clinical applications.